Genomic comparative analysis of Ophiocordyceps unilateralis sensu lato - Lu, Yingling; Tang, Dexiang; Liu, Zuoheng; Zhao, Jing; Chen, Yue; Ma, Jinmei; Luo, Lijun; Yu, Hong (Frontiers in Microbiology, 2024)
Ophiocordyceps unilateralis sensu lato is a common pathogenic fungus of ants. A new species, O. fusiformispora, was described based on morphology and phylogenetic evidence from five genes (SSU, LSU, TET1α, RPB1, and RPB2). The whole genomes of O. fusiformispora, O. contiispora, O. subtiliphialida, O. satoi, O. flabellata, O. acroasca, and O. camponoti-leonardi were sequenced and annotated, as well as compared with whole genome sequences of other species in O. unilateralis sensu lato. The basic genome-wide characteristics of the twelve species showed that the related species had similar GC content and genome size. AntiSMASH and local BLAST analysis revealed that the number and types of putative SM BGCs, NPPS, PKS and hybrid PKS-NRPS domains for the twelve species differed significantly among different species in the same genus. The putative BGC of five compounds, NG-391, lucilactaene, higginsianin B, pyripyropene A and pyranonigrin E were excavated. NG-391 and lucilactaene that were 7-desmethyl analogs of fusarin C. Furthermore, the twelve genomes had common domains, namely KS-AT-DH-MT-ER-KR-ACP and SAT-KS-AT-PT-ACP-ACP-Te. The ML and BI trees of SAT-KS-AT-PT-ACP-ACP-Te were highly consistent with the multigene phylogenetic tree in the twelve species. This study provided a method to obtain the living culture of O. unilateralis sensu lato species and its asexual form on the basis of living culture, which was of great value for further study of O. unilateralis sensu lato species in the future, and also laid a foundation for further analysis of secondary metabolites of O. unilateralis sensu lato.